Findings of Late Antique Oil-lamps Between Krka and Cetina Rivers - Matijević, Vinka (2012)
Territory between Croatian rivers Krka and Cetina is abundant in archaeological sites. There, for almost two centuries, archaeologists are compiling, studying and publishing diverse and rich archaeological material. Published findings include hundreds of whole or fragmented Late Antique oil-lamps. The aim of this paper is to analyze the distribution of these lamps. We made a map that represents the distribution of Late Antique oil-lamps on certain archaeological sites. In addition, we analyzed the frequency of certain types of Late Antique oil-lamps and the most common motifs that occur on their discs. The majority of them originate from Salona, the capital of the Roman Province Dalmatia. A significant number was found in the hinterland of Salona. Besides a lesser number of Late Antique oil-lamps that have no decoration on their discs, majority has different motifs. The standard motifs are: Early Christian symbols, animal motifs, scenes of everyday life, vegetable motifs or geometric shapes that are characteristic in Late Antique period.